Optimization of properties and structure of lightweight materials using digital methods - Igor V. Bessonov; Alexey D. Zhukov; Ekaterina Yu. Bobrova; Elina A. Gorbunova; Ilya S. Govryakov (Нанотехнологии в строительстве)
Introduction. The solution to problems aimed at improving the efficiency of construction is closely linked to the use of lightweight mineral materials, which include mineral fibres, foam glass, cold-curing cellular glass, cellular concrete, and foam gypsum. Methods and materials. The aim of the research is to study the influence of technological factors on the properties of foam gypsum, as well as on the features of the formation of its structure and optimization of its compositions. The basis of the methodology is digital methods of planning, processing results, and their analytical optimization. Results. Based on the analysis of statistical information, it is established that the optimal composition is the one that includes the consumption of dihydrate gypsum of 76.6 kg/m3, the consumption of the polymerizing component of 9.8 kg/m3, and the consumption of the aqueous solution of the foaming agent of 80 kg/m3. This composition corresponds to a softening coefficient of 0.40–0.42; the compressive strength of foam gypsum is 0.75 MPa, and the average density is 320 kg/m3. Discussion. The properties of foam gypsum are determined by its macro- and mi croporosity, as well as the structure of the interpore partitions. The presence of connecting pores, as well as the crystalline structure of the interpore partition, makes the material permeable to vapour-air mixtures, which is a positive factor for acoustic materials. Conclusion. This material can be used for the production of individual products, as well as in low-rise construction of houses using frame-sheathing technology.